Membangun Kepribadian Muslim yang Kuat: Peran Pendidikan Agama Islam dalam Meningkatkan Kesadaran Diri dan Kepatuhan Terhadap Syariat Islam - Najamudin Najamudin; Surahman Hidayat (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Islamic Religious Education in schools plays an important role in shaping Muslim personalities that reflect authentic Islamic values. The main goal is for students to not only practice religious teachings as a routine, but also understand the meaning of every worship they do, both for themselves and their relationship with God. Islamic Religious Education plays a role as the main pillar in shaping Islamic character, with an approach that involves learning religious values ​​consciously and systematically. This study uses a library research method by analyzing various references from journals and books that discuss the role of Islamic Religious Education in character formation. The results of the study show that this education contributes significantly to building a society that has moral responsibility and strong Islamic character. By strengthening faith and piety, students are expected to avoid negative behavior that can damage social life and endanger national unity. Therefore, Islamic Religious Education is a long-term investment in creating individuals who are not only intellectually intelligent, but also have noble morals according to Islamic teachings.